Efek Pemberian Larutan Ekstrak Akar Kayu Kuning terhadap Histopatologi Ginjal Mencit yang Diinduksi D-Galaktosa - Zehan Afifa Yusran; Biomechy Oktomalio Putri; Miftah Irramah; Tofrizal; Liganda Endo Mahata; Novita Ariani (Jurnal Kesehatan Masyarakat Indonesia (JKMI), 2025)
D-galactose is a reducing sugar that induces oxidative stress by increasing the production of Reactive Oxygen Species (ROS) and Advanced Glycation End-products (AGEs), processes also associated with aging. Akar kayu kuning (Arcangelisia flava Merr.) extract contains antioxidant compounds that neutralize free radicals and mitigate oxidative stress. This study aimed to evaluate the effect of akar kayu kuning extract on the histopathological alterations of the kidneys in D-galactose-induced mice (Mus musculus). A true experimental study with a post-test-only control group design was conducted using 25 mice, divided into five groups: a negative control, a positive control (administered D-galactose at 150 mg/kgBW), and three experimental groups that received akar kayu kuning extract at doses of 250 mg/kgBW, 500 mg/kgBW, and 750 mg/kgBW following D-galactose induction. Kidney tissues were stained with hematoxylin and eosin (HE), and the extent of histopathological damage was quantified using ImageJ software. Statistical analysis using the Kruskal-Wallis test revealed significant differences between the experimental groups and the positive control (p < 0.05). The findings demonstrate that akar kayu kuning extract significantly reduces kidney histopathological damage in D-galactose-induced mice, highlighting its potential as a natural antioxidant for preventing oxidative stress-related renal impairment.